Política e comércio: a atuação de Domingos José de Almeida ministro da república sul-rio-grandense e negociante (1830-1850) - Campos, Cristiano Soares (2016)
This Master's thesis was developed at the Graduate Program in History at the Federal University of Santa Maria, integrating the research line "Integration, Policy and Society" and had scholarship aid FAPERGS / CAPES. The objective of this study was to investigate how the political and commercial trajectory of Domingos José de Almeida built in the Brazilian Empire between 1830-1850, during which it has held senior political office in Rio Grande do Sul, as the Councillor, Provincial and Minister Deputy of Finance. For this, we investigated from the marriage with Bernardina Barcelos possible reasons of marriage and relationships crony created from the union, and Domingos Almeida Joseph ascended the social ladder as charqueador and entered local politics in Pelotas region. Almeida was part of the insurgent group that sparked the revolt of the Patches in 1835 and played in activities rag State. Also interested in how and what were the business networks that Almeida was inserted during and after the uprising, noting the relationship between Rio Grande and its neighboring platinum business. Finally we examine the performance of Domingos Jose de Almeida in recent years of the War of Tatters and the end of the conflict as the former Minister of Finance found your finances and what strategies used to recover investments in riograndense republic. We work from the perspective of political history using the sources such as inventory Domingos José de Almeida, correspondence, journals, notes and certificates transmissions, Minutes of the City Council, among others. The research aims to understand how the dynamics of political and trade relations in the path of Domingos José de Almeida, characteristics that perhaps can also be attributed to traders that tumultuous context.